Anthyllis apennina (Fabaceae), a new species from central Apennine (Italy) - Fabio Conti; Fabrizio Bartolucci (PhytoKeys, 2021)
A new species of Anthyllis endemic to central Apennine growing in dry pastures on limestone in the montane belt, within Abruzzo and Lazio administrative regions (central Italy), is here described and illustrated and the IUCN assessment is proposed. This new species belongs to the morphologically very variable Anthyllis vulneraria species complex and it is close to A. pulchella (south-eastern Europe and Caucasus), but it can be clearly distinguished by its smaller flowers, mainly light yellow-coloured, bracts longer than flowers, calyx pink-coloured (usually only at apex) and size of cauline leaves and leaflets. Furthermore, the name A. pulchella is here lectotypified, by a second-step typification, on a specimen preserved at PAD.